2001
DOI: 10.1038/sj.gene.6363723
|View full text |Cite
|
Sign up to set email alerts
|

Linkage analysis of the 5q31–33 candidate region for asthma in 240 UK families

Abstract: Atopy and asthma are complex genetic diseases resulting from the interactions of a number of genetic and environmental factors. We had previously reported allelic association between the IL9 marker on chromosome 5q31-33 and atopy. In order to further investigate the role of susceptibility genes on 5q31-33 in the development of atopy and asthma we have studied 240 UK families comprising 131 families selected at random, 60 multiplex families with affected sib pairs, and 49 single proband nuclear families. Polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…Our initial report of linkage of BHR to chromosome 5q31-q33 in Dutch families with asthma (6) has been confirmed in six other populations for asthma-associated phenotypes (7)(8)(9)(10)(11)(12). This finding has been extended by showing that chromosome 5q31-q33 interacts with ETS exposure in utero and/or early childhood in the development of BHR and asthma (13,14).…”
mentioning
confidence: 48%
“…Our initial report of linkage of BHR to chromosome 5q31-q33 in Dutch families with asthma (6) has been confirmed in six other populations for asthma-associated phenotypes (7)(8)(9)(10)(11)(12). This finding has been extended by showing that chromosome 5q31-q33 interacts with ETS exposure in utero and/or early childhood in the development of BHR and asthma (13,14).…”
mentioning
confidence: 48%
“…53 54 The protective association of the homozygous TC haplotype with asthma, hayfever, and atopy would be consistent with the evidence from genome-wide scans that genes within the 5q31-33 region are not only important in IBD but also in asthma and atopy. [55][56][57][58] Indeed, candidate genes within the 5q31-33 region, including IL12B gene 59 and IL13, 60 have been associated with asthma and atopy.…”
Section: Discussionmentioning
confidence: 99%
“…The ␤ 2 -adrenergic receptor has been linked to asthma and its related phenotypes in several studies of different populations, including families from China, Australia, England, Japan, and the United States. [58][59][60][61][62][63] A study of children from the Netherlands demonstrated that elevated serum IgE levels were coinherited with BHR and these traits were linked to an area on chromosome 5q. 64 Marker D11S97 on chromosome 11q13 was first linked to atopy in 1989, 65 and this association subsequently was demonstrated multiple times.…”
Section: Genetic Basis For Asthmamentioning
confidence: 99%